Developing Guessing Game for Teaching Vocabulary to the Fifth Grade Students of SD Negeri 5 Kubutambahan - Suardiyasa, Komang Gede (Journal of Psychology and Instructions, 2017)
This present study was a research and development (R&D) which concerned in; identifying the kinds of vocabulary were appropriate to be developed as Guessing Game (GG) for teaching vocabulary to the fifth grade of students of SD Negeri 5 Kubutambahan, analyzing the quality of the developed Guessing Game (GG) for teaching vocabulary to the fifth grade of students of SD Negeri 5 Kubutambahan. This study followed the R&D design proposed by Dick and Carey (2005). This design involves: need analysis, instructional analysis, learner and learning environment, performance objectives, assessment rubric, story board, design and develop, formative evaluation, revision and final product. The subjects of the study were students of fifth grade and the teacher of SD Negeri 5 Kubutambahan. the data were collected through observation, questionnaire, interview, document review and expert judgment. The result of the study shows that: (1) there were four guessing games have been developed with four different themes which were aimed to be used as a media for teaching vocabulary to the first semester of 5th grade students. Those guessing game were designed based on the criteria of English syllabus of school based curriculum for the first semester of 5th grade students and also based on criteria of educational app by Lee & Cherner (2015). The final of the guessing game were presented into CD and a manual guide book for teacher. (2) the overall quality of the developed guessing game from the judgment of experts was categorized as excellent (2.73).Â